The maximum security book club : reading literature in a men's prison - Brottman, Mikita, 1966- (Harper, 2016)
"A riveting account of the two years literary scholar Mikita Brottman spent reading literature with criminals in a maximum-security men's prison outside Baltimore, and what she learned from them--Orange Is the New Black meets Reading Lolita in Tehran. On sabbatical from teaching literature to undergraduates, and wanting to educate a different kind of student, Mikita Brottman starts a book club with a group of convicts from the Jessup Correctional Institution in Maryland. She assigns them ten dark, challenging classics--including Conrad's Heart of Darkness, Shakespeare's Macbeth, Stevenson's Dr. Jekyll and Mr. Hyde, Poe's story "The Black Cat," and Nabokov's Lolita--books that don't flinch from evoking the isolation of the human struggle, the pain of conflict, and the cost of transgression. Although Brottman is already familiar with these works, the convicts open them up in completely new ways. Their discussions may "only" be about literature, but for the prisoners, everything is at stake. Gradually, the inmates open up about their lives and families, their disastrous choices, their guilt and loss. Brottman also discovers that life in prison, while monotonous, is never without incident. The book club members struggle with their assigned reading through solitary confinement; on lockdown; in between factory shifts; in the hospital; and in the middle of the chaos of blasting televisions, incessant chatter, and the constant banging of metal doors. Though The Maximum Security Book Club never loses sight of the moral issues raised in the selected reading, it refuses to back away from the unexpected insights offered by the company of these complex, difficult men. It is a compelling, thoughtful analysis of literature--and prison life--like nothing you've ever read before"--